Application of Lean System Principles in Healthcare Services Using Arena Simulation (Journal of University of Babylon for Engineering Sciences, 2019)
This research aims to apply lean principles to the Emergency Department (ED) at Sheikh Zayed Hospital. Lean techniques are used in order to eliminate waste, waits and increased patient satisfaction. Lean defines the wastes but not identify which waste should be eliminated for this reason Arena 14.00 Rockwell simulation software used to analyze the ED performance. Patient's flow chart was created to study the total duration of patients stay in the ED, the waiting time and the utilization of resources based on the lean principles approach. The results identified and concluded from simulation model were as the follows, the patient flow time was (65) minute for each patient (total time that patient spent from the beginning of his entry into the ED until he discharged), while patient throughput in morning shift about (241) patient (the number of patients attending the department during morning hours). On the other hand, the utilization ratio of doctors, nurses, receptionists were (83 %, 13 %, and 95 %) respectively. This is demonstrating the applicability and effectiveness of lean principles to ED processes using the simulation model as a pre-implementation tool for improvements in health care sectors.